TANTANGAN PENGUNAAN INTERNET SEBAGAI SUMBER BELAJAR DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA - Farmah, Farmah (UNTIRTA CIVIC EDUCATION JOURNAL, 2022)
The purpose of this study was to determine the challenges of using the internet as a learning resource in increasing the learning activity of class IX Computer Network Engineering students at SMK Insan Mulya. In this study, the researcher aims to determine the challenge factors and inhibiting factors in using the internet as a learning resource and to determine efforts in dealing with various obstacles and challenges in increasing student learning activity. The research method used is a descriptive qualitative technique. The researcher determined the location of the study as the place where the study would be conducted at SMK Insan Mulya. The research location is located in Tambak Village, Kibin District, Serang Regency, Banten. With the results of the study that the challenges of using the internet as a learning resource at SMK Insan Mulya are inadequate networks and limited facilities, this is due to various factors, namely inadequate school facilities provided, the unavailability of an internet network at school, economic factors of students' families who do not all have laptops or gadgets as learning resources, and factors of educators and the classroom environment. The efforts made to maximize learning activities in the classroom are that the school provides adequate facilities for the learning process in the classroom, as well as the use of models, media and varied learning methods in the teaching and learning process in the classroom so that it can increase student learning activity.